Examining the Prospective Relationship between Family Affective Responsiveness and Theory of Mind in Chronic Paediatric Traumatic Brain Injury. Issue 1 (11th October 2016) - Ryan, Nicholas P.; Mihaljevic, Kim; Beauchamp, Miriam H.; Catroppa, Cathy; Crossley, Louise; Hearps, Stephen; Silk, Timothy; Godfrey, Celia; Yeates, Keith Owen; Anderson, Vicki A.
Abstract : Childhood and adolescence coincide with rapid structural and functional maturation of brain networks implicated in Theory of Mind (ToM); however, the impact of paediatric traumatic brain injury (TBI) on the development of these higher order skills is not well understood. ToM can be partitioned into conative ToM, defined as the ability to understand how indirect speech acts involving irony and empathy are used to influence the mental or affective state of the listener; and affective ToM, concerned with understanding that facial expressions are often used for social purposes to convey emotions that we want people to think we feel. In a sample of 84 children with mild-severe TBI and 40 typically developing controls, this study examined the effect of paediatric TBI on affective and conative ToM; and evaluated the respective contributions of injury-related factors (injury severity/lesion location) and non-injury-related environmental variables (socio-economic status (SES)/family functioning) to long-term ToM outcomes. Results showed that the poorest ToM outcomes were documented in association with mild-complicated and moderate TBI, rather than severe TBI. Lesion location and SES did not significantly contribute to conative or affective ToM. Post-injury family affective responsiveness was the strongest and most significant predictor of conative ToM. Results suggest that clinicians should exercise caution when prognosticating based on early clinical indicators, and that group and individual-level outcome prediction should incorporate assessment of a range of injury- and non-injury-related factors. Moreover, the affective quality of post-injury family interactions represents a potentially modifiable risk factor, and might be a useful target for family-centred interventions designed to optimise social cognitive outcomes after paediatric TBI.